Cartilage-Specific 18F-NaF Uptake in Rat Models: A Multimodal In Vitro and Ex Vitro Comparative Study with 99mTc-MDP - Qingxiao Li; Jianpeng Gao; Yiqun Wang; Yaoyao Song; Liwei Liu; Cong Zhang; Ming Li; Haodan Dang; Jiahe Tian (Biomedicines)
Background: 18F-NaF and 99mTc-MDP are widely used bone imaging tracers, but their comparative uptake in bone versus cartilage is unclear. This study aimed to directly compare these patterns in rats to guide musculoskeletal molecular imaging. Methods: Male Sprague-Dawley rats underwent in vivo and ex vivo radiotracer studies. Tracer uptake (%ID/g) was quantified in bone and cartilage at 30, 60, or 120 min post-injection (18F-NaF or 99mTc-MDP), and across different ages. Additional rats received subcutaneous implants of viable or devitalized bone and cartilage; uptake was assessed using PET/CT, autoradiography, and histology. Results: 18F-NaF showed faster blood/background clearance and higher target-to-background ratios compared to 99mTc-MDP, especially in weight-bearing joint cartilage. 18F-NaF uptake in cancellous bone significantly exceeded that of 99mTc-MDP, whereas 99mTc-MDP showed higher uptake in knee cartilage. Age-related analysis showed maximal knee cartilage accumulation in aged rats. Histological and cell inactivation studies confirmed that 18F-NaF uptake reflects both cellular activity and degree of calcification. Conclusions:18F-NaF demonstrates distinctive, quantifiable uptake in cartilage, dependent on both cellular activity and calcification, and exhibits favorable imaging characteristics versus 99mTc-MDP for cartilage metabolism. These findings support 18F-NaF as a promising tool for early diagnosis and therapeutic monitoring of bone and joint disorders, and provide pathophysiological insight into the dynamics of the bone–cartilage interface.